Systematical Analysis on angular Distribution of Bremsstrahlung radiation in microtron MT-22 - B. Otgooloi; N. Enkhbat; J. Oyunbileg (Scientific transaction of the National University of Mongolia. Physics, 2022)
The systematic analysis has been made the measurement results of the relative angular distribution of gamma quantium with 11-22 MeV energy which is induced by bremsstrahlung within 2-3 g/cm optimal geometrical region of target nucleus. We are shown that relative intensity distribution of gamma radiation with energy 11-22 MeV, induced by stopped electrons with various thicknesses at heavy and lighter target nucleus as an exponential form within angular region 0°-14o